2015
DOI: 10.1111/eve.12407
|View full text |Cite
|
Sign up to set email alerts
|

Horses, saddles and riders: Applying the science

Abstract: An enthusiastic crowd of 400 people gathered at Anglia Ruskin University in Cambridge, UK on 29 November 2014 for the second International Saddle Research Trust Conference on the theme of Horses, Saddles and Riders: Applying the Science. The conference was organised under the auspices of the Saddle Research Trust (SRT) which is a charitable organisation based in the UK established with the intention of stimulating and supporting research into the influence of saddles on the welfare, performance and safety of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Rider body size relative to the horse is a potential issue, but is dependent on many factors including the type, speed and duration of work and rider skill and balance (Clayton et al 2015). The veterinary profession is in a position to provide advice concerning rider size and bodyweight relative to horse size and type.…”
Section: Other Saddle Fit Accessoriesmentioning
confidence: 99%
“…Rider body size relative to the horse is a potential issue, but is dependent on many factors including the type, speed and duration of work and rider skill and balance (Clayton et al 2015). The veterinary profession is in a position to provide advice concerning rider size and bodyweight relative to horse size and type.…”
Section: Other Saddle Fit Accessoriesmentioning
confidence: 99%
“…In order to understand the process of veterinary examination and its resultant observations; it is imperative to fully understand the kinematics and kinetics of the locomotion of the horse. The structure and function of the cursorial musculoskeletal systems have evolved to provide structures and patterns of movement that favour acceleration, manoeuvrability speed and endurance [30,37,38] which has been harnessed over centuries for various disciplines such as racing and dressage.…”
Section: Kinematics and Kinetics Of Locomotionmentioning
confidence: 99%
“…Therefore, it is worth considering the kinematic pattern of hoof placement, to determine how the pathology of SID and hindlimb PSD may occur. The structure and function of the cursorial musculoskeletal systems have evolved to provide structures and patterns of movement that favour acceleration, manoeuvrability speed and endurance [30,37].…”
Section: Kinematics and Kinetics Of Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal advocacy informants in the same study additionally identified routine training and husbandry practices, human-horse interactions and the “everyday life of horses” as “where the real welfare issues are” in thoroughbred racing [ 3 ]. These are issues discussed in the general equine welfare literature and include topics such as housing [ 4 , 5 , 6 , 7 ], feeding [ 8 , 9 ], equine behaviour [ 10 ], equine emotions [ 11 ], equine welfare assessment [ 12 , 13 ], the application of equipment [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], equine learning and training [ 22 , 23 ], the impact of equine activities on the horse [ 24 ], human handling during various forms of human-horse interactions [ 25 , 26 ], impacts of riding on behaviour and welfare [ 27 , 28 , 29 , 30 ], horse-human relationships [ 31 , 32 , 33 , 34 ] and people’s ability and inability to recognise behavioural signs of equine distress and pain [ 35 , 36 , 37 , 38 ]. A theme that unites these issues and that allows one to make assessments as to the welfare impact is naturalness, i.e., what is natural for the horse and what is in the horse’s nature in relation to their species-specific, as well as individual, physiological; emotional; cognitive; social and behavioural characteristics, abilities and boundaries.…”
Section: Introductionmentioning
confidence: 99%